2002
DOI: 10.1046/j.1532-5415.2002.50009.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Geographic Barriers on the Utilization of Mammograms by Older Rural Women

Abstract: The majority of Kansans live near a mammography facility. Although there is a large variation in county-level mammography rates across Kansas, this disparity is not well explained by proximity to mammography facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 29 publications
3
81
1
Order By: Relevance
“…This is not consistent with prior literature that shows rural populations have lower opportunity and participation rates 5, 22, 23, 24, 25, 26. This unexpected finding could be influenced by the extensive community‐based participatory research capacity that the states only academic medical center (University of Arkansas for Medical Sciences) had invested in to better engage rural and minority participants.…”
Section: Discussioncontrasting
confidence: 88%
“…This is not consistent with prior literature that shows rural populations have lower opportunity and participation rates 5, 22, 23, 24, 25, 26. This unexpected finding could be influenced by the extensive community‐based participatory research capacity that the states only academic medical center (University of Arkansas for Medical Sciences) had invested in to better engage rural and minority participants.…”
Section: Discussioncontrasting
confidence: 88%
“…Two studies, including one in a major metropolitan area, have found that people who lived farther away from facilities were less likely to undergo mammography than those who lived closer to facilities. 29,30 Another found no association between distance or travel time and compliance with screening mammography recommendations in rural Michigan. 31 Most studies of the association between distance and health care utilization have examined this relationship among residents of rural areas or large regions such as states that include areas of varying rurality.…”
Section: Introductionmentioning
confidence: 98%
“…However, later local studies have found no rural and urban differences in mammography screening. For example, geographic differences were not a barrier in getting mammograms in studies conducted in the Upper Peninsula of Michigan [22] or among older women in Kansas [23].…”
Section: Introductionmentioning
confidence: 99%